The Ethics of Cryonics Is it Immoral to be Immortal? - Minerva, Francesca (Springer International Publishing, 2018)
Cryonics-also known as cryopreservation or cryosuspension-is the preservation of legally dead individuals at ultra-low temperatures. Those who undergo this procedure hope that future technology will not only succeed in reviving them, but also cure them of the condition that led to their demise. In this sense, some hope that cryopreservation will allow people to continue living indefinitely. This book discusses the moral concerns of cryonics, both as a medical procedure and as an intermediate step toward life extension. In particular, Minerva analyses the moral issues surrounding cryonics-related techniques (including the hypothetical cryosuspension of fetuses as an alternative to abortion) by focusing on how they might impact the individuals who undergo cryosuspension, as well as society at large. .